Growth and volatility regime switching models for New Zealand GDP data - Robert A Buckle; David Haugh; Peter Thomson (New Zealand Government, The Treasury, 2002)
This paper fits hidden Markov switching models to New Zealand GDP data. A primary objective is to better understand the utility of these methods for modelling growth and volatility regimes present in the New Zealand data and their interaction. Properties of the models are developed together with a description of the estimation methods, including use of the Expectation Maximisation (EM) algorithm. The models are fitted to New Zealand GDP and production sector growth rates to analyse changes in their mean and volatility over time. The paper discusses applications of the methodology to identifying changes in growth performances, and examines the timing of growth and volatility regime switching between production sectors. Conclusions to emerge are that, in contrast to the 1980s, New Zealand GDP growth experienced an unusually long period of time in high growth and low volatility regimes during the 1990s. The paper evaluates sector contributions to this 1990s experience and discusses directions for further development.
Keywords: C22; E23; E32; O47; 330; Hidden Markov models; regime switching; growth; business cycles; volatility; production sectors; GDP.